Corporate governance, corporate social responsibility and the corporation's purpose - Michael Roumeliotis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: To rethink the idea that corporate governance is about the alignment of interests of all stakeholders. To indicate this idea's main problems, in making the manager's job significantly more difficult, and in creating numerous avenues for managers seeking merely to advance their own interests. To look into corporate social responsibility in the light of value rationality, and to understand that taking into account stakeholders' interests may be extraneous to purpose rationality and to the corporation's purpose. To indicate this main difference between a corporation as a juristic person of limited purpose on the one hand, and a state government on the other. To relate these ideas to Freeman's "new story of business" and to the declaration that profits are an outcome of successful business rather than its purpose. Design/methodology/approach: The approach is conceptual/ philosophical. Findings: The stakeholder theory of corporate governance is misguided, insofar as it is taken to assume that the purpose of the corporation is to serve the various interests of all stakeholders. Considerations of corporate social responsibility may (and should) be understood as value rational, having little bearing on the corporation's purpose, i.e. shareholders' profit, but placing essential constraints on the means of its achievement. This however should not be seen as being at odds with Freeman's "new story of business". Research limitations/implications: The "stakeholder theory of corporate governance" may be construed (in light of the above) as placing the interests of stakeholders other than the shareholders, outside the corporation's purpose. History may result in corporations taking over parts of government, thus integrating common good in the corporations' purpose from a normative point of view. Originality/value: The application of the distinction between value rationality and purpose rationality, to what CSR means for the purpose of the corporation and for stakeholder theory, is totally original, and so is the main conclusion of the argument. Summary: The original core problem of corporate governance is the agency problem and the alignment of interests between managers and shareholders, under the principle that the purpose of the corporation that managers ought to serve is shareholders' profit. The idea of corporate social responsibility has brought about stakeholder theory, that is the idea that corporate governance is about serving all stakeholders' interests. This multiplies the conflicts of interests to be aligned and creates in effect many more avenues for managers seeking to advance their own interests. We present an example of a board of directors seeking to allocate a substantial part of the corporation's wealth to the alleviation of social poverty, and we revisit the question of the purpose of the corporation as a legal boundary to the possibilities of the juristic person that is the corporation. We advance the idea that corporate social responsibility and taking stakeholders other than shareholders into account is about value rationality, not purpose rationality, and should not be understood as necessarily depending on long term profit or any win/win situations. It mostly places constraints on the purpose rational means to achieve the corporation's purpose, which remains shareholders' profit. It must not be understood to alter this purpose, nor to make the corporation assume a social role paralleling state government. Freeman's advocacy of the "new story of business", and his concomitant ideas that business is about the business idea rather than profit, that people are not primarily driven by greed, that stakeholder relationships are crucial for business, and that creative imagination in balancing all values and interests is at the root of greater value creation, are in fact perfectly reconcilable with the above.
Keywords: K20; L20; M14; 330; Corporate Governance; CSR; Stakeholder Theory; Value Rationality; Purpose; Rationality